2012
DOI: 10.1039/c1py00380a
|View full text |Cite
|
Sign up to set email alerts
|

Direct nitroxide mediated (co)polymerization of 4-vinylphenylboronic acid as route towards sugar sensors

Abstract: The controlled polymerization of the unprotected, commercially available, 4-vinylphenylboronic acid (4-VBA) monomer is reported by nitroxide mediated polymerization. The glucose responsive pH window of poly(4-VBA) is reported based on turbidimetry. Finally, poly(4-VBA) polymeric pH sensors have been developed by the incorporation of solvatochromic dyes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 26 publications
1
51
0
Order By: Relevance
“…This is part of a larger research field, namely functionalized polymers. [13][14][15][16] It has been shown that pH…”
Section: Introductionmentioning
confidence: 99%
“…This is part of a larger research field, namely functionalized polymers. [13][14][15][16] It has been shown that pH…”
Section: Introductionmentioning
confidence: 99%
“…The VPBA segments of the copolymer were not soluble in aqueous solution due to strong hydrogen bonding between the boronic acid moieties and the transition to the tetragonal anionic form that occurs around pH 8 to 10 in the presence of glucose. 57 As expected, the CPT decreased with an increase of VPBA content in the final copolymer and it was 28.0 to 36.4 8C (at 0.5 wt % solution concentration) with F VPBA 5 0.045 to 0.13 (approximately a degree decrease in CPT per 1 mol % of increase in VPBA content). In previous studies of a similar system where MEMA was copolymerized with VBK via NMP, the CPTs of the resulting copolymers were affected by composition and ranged between 37 and 43 8C.…”
Section: Complexation Of Boron With the Tertiary Aminementioning
confidence: 63%
“…Controlled homopolymerization of VPBA by NMP has been reported in the presence of BlocBuilder initiator previously. 57 Figure 2 shows the characteristic kinetic plots of log ((1 2 X) 21 ), versus time and Figures 3 and 4 shows M n and -D, respectively, versus conversion for all copolymerizations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This translational mechanism has mostly been used for the creation of polymeric thermometers with examples including a 1,8-naphthalimide-decorated thermoresponsive copolymer like poly( N -isopropylacrylamide) showing fluorescent enhancement upon precipitation [83] or Disperse Red 1 (DR1)-oligoethyleneglycol acrylate copolymers showing a bathochromic shift [84,85]. The possibility of using a solvatochromic dye for the creation of polymeric sensors for glucose was published by our group in 2012 where the pH-induced polymer precipitation of a P(4-VBA) was translated into a color change by incorporating DR1 [86]. …”
Section: Sensory Applicationsmentioning
confidence: 99%